2015
DOI: 10.1167/iovs.15-17521
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Prosthetic and Natural Vision in Animals With Local Retinal Degeneration

Abstract: PURPOSE. Prosthetic restoration of partial sensory loss leads to interactions between artificial and natural inputs. Ideally, the rehabilitation should allow perceptual fusion of the two modalities. Here we studied the interactions between normal and prosthetic vision in a rodent model of local retinal degeneration.METHODS. Implantation of a photovoltaic array in the subretinal space of normally sighted rats induced local degeneration of the photoreceptors above the chip, and the inner retinal neurons in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
(28 reference statements)
3
11
0
Order By: Relevance
“…This could be attributed to the specifics of the visual system microcircuit that the stimulation electrode activated. This modulation of cortical response is consistent with the results from experiments 15 , 16 , 40 with subretinal photovoltaic stimulation, which showed that increasing the stimulus intensity (of the near-infrared light used to stimulate the photovoltaic cells) increases cortical response.…”
Section: Discussionsupporting
confidence: 89%
“…This could be attributed to the specifics of the visual system microcircuit that the stimulation electrode activated. This modulation of cortical response is consistent with the results from experiments 15 , 16 , 40 with subretinal photovoltaic stimulation, which showed that increasing the stimulus intensity (of the near-infrared light used to stimulate the photovoltaic cells) increases cortical response.…”
Section: Discussionsupporting
confidence: 89%
“…Prosthetic contrast sensitivity was 5–6 times worse than natural at all contrast levels, and it remains unknown whether positive and negative contrast steps in prosthetic stimulation were perceptually distinct in animals that responded behaviorally to both onset and offset of light. Lack of response to prosthetic stimulation in WT rats indicates that 1) the infrared stimulation does not elicit any visual response or 2) that the prosthetic stimulation may be competing with normal vision – as predicted by earlier VEP measurements 36 .…”
Section: Discussionmentioning
confidence: 77%
“…Non-implanted animals did not respond to photovoltaic stimulation at any settings, confirming that the response was elicited by the implant rather than by perception of the infrared light. Normally sighted rats (LE) with photovoltaic implants did not respond to stimulation either, suggesting that normal vision in our experimental paradigm (room lights on) dominates the small prosthetic input 21 , and thereby eliminates the startling response observed in blind animals lacking any additional visual information.
Figure 1 Behavioral determination of the stimulation thresholds.
…”
Section: Resultsmentioning
confidence: 94%
“…Future studies with longer follow up will determine if this phenomenon is transitory. Indeed, the absence of contact between RPE and photoreceptors, as observed in the case of electronic implants grafting between RPE and photoreceptors in rats (40,41) can lead photoreceptors to quickly degenerate. In our previous experiments in the Royal College of Surgeons rat presenting a specific defect in the phagocytosis function of endogenous RPE that engenders the accumulation of OS debris and photoreceptor cell death, we observed that the hESC-RPE sheet sustained the photoreceptor survival during the 3-month follow up which indicates that grafted cells were able to eliminate photoreceptor OS debris and prevent their death (22).…”
Section: Discussionmentioning
confidence: 99%